If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = (6y + 2) + -1(y + -5)(-2y + 16) Reorder the terms: 16 = (2 + 6y) + -1(y + -5)(-2y + 16) Remove parenthesis around (2 + 6y) 16 = 2 + 6y + -1(y + -5)(-2y + 16) Reorder the terms: 16 = 2 + 6y + -1(-5 + y)(-2y + 16) Reorder the terms: 16 = 2 + 6y + -1(-5 + y)(16 + -2y) Multiply (-5 + y) * (16 + -2y) 16 = 2 + 6y + -1(-5(16 + -2y) + y(16 + -2y)) 16 = 2 + 6y + -1((16 * -5 + -2y * -5) + y(16 + -2y)) 16 = 2 + 6y + -1((-80 + 10y) + y(16 + -2y)) 16 = 2 + 6y + -1(-80 + 10y + (16 * y + -2y * y)) 16 = 2 + 6y + -1(-80 + 10y + (16y + -2y2)) Combine like terms: 10y + 16y = 26y 16 = 2 + 6y + -1(-80 + 26y + -2y2) 16 = 2 + 6y + (-80 * -1 + 26y * -1 + -2y2 * -1) 16 = 2 + 6y + (80 + -26y + 2y2) Reorder the terms: 16 = 2 + 80 + 6y + -26y + 2y2 Combine like terms: 2 + 80 = 82 16 = 82 + 6y + -26y + 2y2 Combine like terms: 6y + -26y = -20y 16 = 82 + -20y + 2y2 Solving 16 = 82 + -20y + 2y2 Solving for variable 'y'. Combine like terms: 16 + -82 = -66 -66 + 20y + -2y2 = 82 + -20y + 2y2 + -82 + 20y + -2y2 Reorder the terms: -66 + 20y + -2y2 = 82 + -82 + -20y + 20y + 2y2 + -2y2 Combine like terms: 82 + -82 = 0 -66 + 20y + -2y2 = 0 + -20y + 20y + 2y2 + -2y2 -66 + 20y + -2y2 = -20y + 20y + 2y2 + -2y2 Combine like terms: -20y + 20y = 0 -66 + 20y + -2y2 = 0 + 2y2 + -2y2 -66 + 20y + -2y2 = 2y2 + -2y2 Combine like terms: 2y2 + -2y2 = 0 -66 + 20y + -2y2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-33 + 10y + -1y2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-33 + 10y + -1y2)' equal to zero and attempt to solve: Simplifying -33 + 10y + -1y2 = 0 Solving -33 + 10y + -1y2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 33 + -10y + y2 = 0 Move the constant term to the right: Add '-33' to each side of the equation. 33 + -10y + -33 + y2 = 0 + -33 Reorder the terms: 33 + -33 + -10y + y2 = 0 + -33 Combine like terms: 33 + -33 = 0 0 + -10y + y2 = 0 + -33 -10y + y2 = 0 + -33 Combine like terms: 0 + -33 = -33 -10y + y2 = -33 The y term is -10y. Take half its coefficient (-5). Square it (25) and add it to both sides. Add '25' to each side of the equation. -10y + 25 + y2 = -33 + 25 Reorder the terms: 25 + -10y + y2 = -33 + 25 Combine like terms: -33 + 25 = -8 25 + -10y + y2 = -8 Factor a perfect square on the left side: (y + -5)(y + -5) = -8 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4(8x+3)-5=2(6x+8)+1 | | 5+x+7= | | 3.1x+2.9x=-6 | | -17y-9y+18=-8 | | x+y+z+u=10 | | z=50x+60y | | 10x-17=6x+2 | | 5(m-3)=7 | | 5m+7=5m+s+1 | | 9x+3x-4x=54 | | x+6.3=9.9 | | 16b-6.5=8.5 | | 6(2a+7)-10= | | 9(x-5)+8= | | 8In(3x)=32 | | 6(x+7)-20=6y | | -8x+2x-16-5x+7x= | | 24=14+3(x+8) | | 60=2d+d+30 | | 5x+6x+3+8=7x+5+3x | | -0.6*6= | | Y=20sin(3x) | | 2b-4-4b-6= | | 6a-3c= | | 36x-4=4x | | 8-(2+x)=0 | | 59-2x=5-8x | | X^2-3x=-2.25 | | 5x^3+8x^2-2=0 | | 6(a+8)=56 | | 90=5x+3y | | Y=4(x+45)+3x |